Evaluation of user experience on collaborative learning game / Hasmira Mohamed - Mohamed, Hasmira (2014)
Collaboration and cooperation are the underlying activities which are essential for the development of better interaction and communication between humans. Collaborative learning games have evolved significantly over recent years and also with improvements. However, there are not many researchers out there do evaluation on collaborative learning games to identify the user experience when people play games which allows them to collaborate with others. Therefore, the purpose of this study is to evaluate one of the collaborative learning game (2 Player Reactor) which focusing on the user experience when they play the game. This evaluation is also conducted to map the design principles for future development of better collaborative learning games from the output obtained from this research. There are two methods that has been conducted to obtain results for this study which are observation (video recording) and conducting informal interview with children. The behavior and emotions of children when they experience the collaborative learning game are observed and recorded. The data is then analyzed to identify the children's experience when they are allowed to play a learning game together with their friends. Researcher is about to examine the effectiveness of this game towards the development of learning skills as well as the interaction promoted when they experience the collaborative game. The interview with the participants are required to support the analysis made on the truthfulness of user experience when they play the collaborative game and also to suggest new features that should be implemented to the game. From the results, it was found that the collaborative game is able to increase learning performance among children in which it attracts them to play the game by promoting competitive element and generates fun among them.